Manajemen paud (pendidikan anak usia dini) : pendidikan taman kehidupan anak / Hj. Ihsana El-Khuluqo ; editor, Suwarno - IHSANA EL-KHULUQO, Hj, 1957-; Suwarno (Pustaka Pelajar, 2015)
xix, 194 hlm. ; 23 cm